Mycobacterium tuberculosis Rv1515c antigen enhances survival of M. smegmatis within macrophages by disrupting the host defence. (April 2021) - Yang, Wenmin; Liu, Minqiang; Yu, Xi; Huang, Yu; Zeng, Jie; Dai, Yongdong; Luo, Hongping; Huang, Qinqin; Fan, Lin; Xie, Jianping
Abstract: Mycobacterium tuberculosis ( Mtb ) infection is the major cause of tuberculosis. Mtb regions of difference (RD) genes are vital for survival of the pathogen within hosts and for the attenuation of the bacillus Calmette–Guérin vaccine. However, the function of most RD proteins largely remains unexplored. In the present study, we focused on Rv1515c, an RD6 member from M. tuberculosis, and characterised it as a cell surface-associated protein that functions in disrupting the cytokine profile and promoting endoplasmic reticulum stress-mediated apoptosis. Rv1515c expression in M. smegmatis, a nonpathogenic species, resulted in enhanced resistance of the bacterium to various in vitro stressors (such as low pH, sodium dodecyl sulfate, oxidative pressure, and nitrogen intermediate) and its cellular survival within macrophages. Our study is the first to identify the role of Rv1515c in the physiology and pathogenesis of mycobacterium. Highlights: This study is the first to identify the immune function of Rv1515c, which belongs to RD6 region. Rv1515c enhanced resistance of the M. smegmatis to various in vitro stressors. Ms_Rv1515c inhibited the expression of proinflammatory cytokines IL-6, IL-1β, TNF-α, and IL12p40. Ms_Rv1515c induced endoplasmic reticulum stress and promoted apoptosis of macrophages.